Early mortality in patients with kidney failure starting chronic dialysis in Zambia: a retrospective cohort analysis - Banda, Justor; Bulaya, Tela; Mweemba, Aggrey; Mweene, Morgan; Suwilanji, Nambaya; Natasha, Chenga; Siziya, Seter (African Journal of Nephrology, 2022)
Introduction: Dialysis is the primary kidney replacement therapy for patients with kidney failure in sub-Saharan Africa. We assessed the rates and predictors of early mortality in Zambian patients starting chronic dialysis. Methods: This retrospective study included all patients who started chronic haemodialysis (HD) or peritoneal dialysis (PD) between 1 January 2017 and 31 August 2020 at the three largest public dialysis centres in Zambia. Data on clinical, laboratory and dialysis characteristics were extracted from medical records. The primary outcome of interest was the mortality rate at 90 days. Results: A total of 154 patients were included in the study; 43.5% were female and 32% were 50 years or older. The main causes of kidney failure were hypertension (59%), glomerulonephritis (10%), HIV/AIDS (10%) and unknown (8%). The mortality rate at 90 days was 12.3%. Of these, 42% were cardiovascular-related mortalities and 32% died of infection related to central venous catheters. The lymphocyte percentage of total white blood cells was lower in patients who died compared to survivors (12.7 vs 20.8%) and was an independent predictor of early mortality (OR 0.914, 95% CI 0.850–0.983; P = 0.015). Conclusions: Early mortality was high in Zambian patients starting dialysis, and a low lymphocyte percentage was a predictor of mortality.